Polyether-ether-ketone composite material as well as preparation method and application thereof
By adding specific ratios of polytetrafluoroethylene and porous glass microbeads to the polyether etherketone composite, the problem of poor wear resistance and breathability is solved, and the low coefficient of friction and excellent wear resistance and breathability is achieved, which is suitable for applications in complex working environments.
Patent Information
- Application Number
- CN202411792301.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-28
AI Technical Summary
The existing polyether ether ketone composite materials have poor wear resistance and breathability, and cannot meet the requirements in complex working environments.
By adding a specific ratio of polytetrafluoroethylene and porous glass microbeads to polyether etherketone, the self-lubricity of polytetrafluoroethylene and the porous structure of porous glass microbeads are used to form a synergistic composite material.
It achieves the low coefficient of friction, excellent wear resistance and excellent breathability of polyether etherketone composite materials, and is suitable for seals, bearings and sliding structural parts in complex working environments.
Smart Images

Figure BDA0005175590220000061 
Figure BDA0005175590220000071
Abstract
Description
Technical Field
[0001] The present invention relates to the field of functional materials, and in particular to a polyetheretherketone composite material and a preparation method and application thereof. Background Art
[0002] In the fields of electricity, medical treatment, aerospace and precision machinery, the performance requirements of materials are increasing day by day, especially in applications such as seals, bearings and sliding structures, which require materials to have both wear resistance and air permeability to adapt to complex working environments. At present, polyetheretherketone (PEEK) is widely used due to its excellent heat resistance, corrosion resistance and mechanical strength, but its friction coefficient is large and friction heat is not easy to dissipate. In order to reduce the friction coefficient of PEEK, some self-lubricating additives such as polytetrafluoroethylene (PTFE), graphite, molybdenum disulfide (MoS2) are usually added to PEEK, but the resulting composite material still has the problem of poor wear resistance. In addition, the addition of these self-lubricating additives cannot increase the air permeability of the composite material, so in applications where air permeability is required, the limitations of traditional composite materials are more obvious.
[0003] In summary, the composite materials in the prior art have poor wear resistance and air permeability and cannot meet the requirements in complex working environments. Therefore, it is urgent to develop a new type of composite material that can have both excellent wear resistance and air permeability. Summary of the invention
[0004] The main purpose of the present invention is to provide a polyetheretherketone composite material and a preparation method and application thereof, so as to solve the problems of poor wear resistance and air permeability of the polyetheretherketone composite material in the prior art.
[0005] In order to achieve the above-mentioned object, according to one aspect of the present invention, a polyetheretherketone composite material is provided, which comprises 50-70wt% polyetheretherketone, 25-35wt% polytetrafluoroethylene and 5-15wt% porous glass microbeads; the porous glass microbeads comprise first porous glass microbeads and second porous glass microbeads, and the mass ratio of the first porous glass microbeads is (20-40):(80-60); wherein the average particle size of the first porous glass microbeads is 1-5μm, and the average particle size of the second porous glass microbeads is 20-30μm.
[0006] Furthermore, the average pore diameter of the first porous glass microbeads is 20-50 nm.
[0007] Furthermore, the average pore diameter of the second porous glass microbeads is 60-100 nm.
[0008] Furthermore, the polyetheretherketone includes at least one of PEEK-G-A2, PEEK-G-A3, and PEEK-G-A4.
[0009] Furthermore, the type of polytetrafluoroethylene is PTFE SM 031.
[0010] Furthermore, the polyetheretherketone composite material includes 55-65wt% of polyetheretherketone, 28-32wt% of polytetrafluoroethylene and 7-13wt% of porous glass microbeads.
[0011] Furthermore, the mass ratio of the first porous glass microbeads to the second porous glass microbeads is (25-35):(75-65).
[0012] According to another aspect of the present invention, a method for preparing the polyetheretherketone composite material provided in the first aspect is provided, comprising the following steps: mixing polyetheretherketone, polytetrafluoroethylene, a first porous glass microbead and a second porous glass microbead; and then performing melt granulation to obtain the polyetheretherketone composite material.
[0013] Furthermore, the temperature of the melt granulation is 340-400°C.
[0014] According to a third aspect of the present invention, there is provided a use of the polyetheretherketone composite material provided in the first aspect or the polyetheretherketone composite material obtained by the preparation method provided in the second aspect in seals and / or bearings.
[0015] Applying the technical solution of the present invention, the present application utilizes the self-lubricating property of polytetrafluoroethylene and the porous structure of porous glass microbeads, and through the synergistic effect between polyetheretherketone, polytetrafluoroethylene and porous glass microbeads of a specific mass ratio, the polyetheretherketone composite material not only has a lower friction coefficient and excellent wear resistance, but also has excellent air permeability. Especially when two porous glass microbeads of different particle sizes are compounded and used in a specific mass ratio, the two cooperate with each other to form a pore network, further improving the air permeability of the polyetheretherketone composite material. The polyetheretherketone composite material provided by the present application can be applied to seals, bearings and sliding structural parts in complex working environments. DETAILED DESCRIPTION
[0016] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0017] As analyzed in the background technology of this application, the polyetheretherketone composite material in the prior art has the problem of poor wear resistance and air permeability. In order to solve this problem, this application provides a polyetheretherketone composite material and a preparation method and application thereof.
[0018] In a typical embodiment of the present application, a polyetheretherketone composite material is provided, which includes 50-70wt% polyetheretherketone, 25-35wt% polytetrafluoroethylene and 5-15wt% porous glass beads; the porous glass beads include first porous glass beads and second porous glass beads, and the mass ratio of the two is (20-40): (80-60); wherein the average particle size of the first porous glass beads is 1-5μm, and the average particle size of the second porous glass beads is 20-30μm.
[0019] The present application utilizes the self-lubricating property of polytetrafluoroethylene and the porous structure of porous glass microbeads, and through the synergistic effect between polyetheretherketone, polytetrafluoroethylene and porous glass microbeads of a specific mass ratio, the polyetheretherketone composite material not only has a lower friction coefficient and excellent wear resistance, but also has excellent air permeability. Especially when two porous glass microbeads with different particle sizes are compounded and used in a specific mass ratio, the two cooperate with each other to form a pore network, further improving the air permeability of the polyetheretherketone composite material. The polyetheretherketone composite material provided in the present application can be applied to seals, bearings and sliding structural parts in complex working environments.
[0020] Typically but not limitatively, in the polyetheretherketone composite material provided in the present application, the content of polyetheretherketone is 50wt%, 55wt%, 60wt%, 65wt%, 70wt% or a range consisting of any two numerical values; the content of polytetrafluoroethylene is 25wt%, 28wt%, 30wt%, 32wt%, 35wt% or a range consisting of any two numerical values; the content of porous glass microbeads is 5wt%, 7wt%, 10wt%, 13wt%, 15wt% or a range consisting of any two numerical values.
[0021] Typically but not limitatively, in the porous glass microbeads provided in the present application, the mass ratio of the first porous glass microbeads to the second porous glass microbeads is, for example, 20:80, 25:75, 30:70, 35:65, 40:60 or a range consisting of any two values.
[0022] Typically but not limiting, the average particle size of the first porous glass microbeads is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or a range consisting of any two values; the average particle size of the second porous glass microbeads is 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, 30 μm or a range consisting of any two values.
[0023] In order to further enhance the air permeability of the polyetheretherketone composite material, the average pore diameter of the first porous glass microbeads is preferably 20 to 50 nm.
[0024] Typically but not limiting, the average pore size of the first porous glass microbeads is 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, or a range consisting of any two of these values.
[0025] In order to further enhance the air permeability of the polyetheretherketone composite material, the average pore diameter of the second porous glass microbeads is 60-100 nm.
[0026] Typically but not limiting, the average pore size of the second porous glass microbeads is 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, or a range consisting of any two of these values.
[0027] In some embodiments, the polyetheretherketone is selected from the PEEK-G products specified in GB / T 41873-2022, such as any one or more of PEEK-G-A2, PEEK-G-A3, and PEEK-G-A4.
[0028] In some embodiments, the type of polytetrafluoroethylene is PTFE SM 031, which complies with the requirements of HG / T2902-1997, such as an average particle size of 100 μm to 260 μm and a volume density of 400 g / L to 600 g / L.
[0029] Typically but not limiting, the average particle size of polytetrafluoroethylene is 100 μm, 120 μm, 140 μm, 160 μm, 180 μm, 200 μm, 220 μm, 240 μm, 260 μm or a range consisting of any two values; the volume density of polytetrafluoroethylene is 400 g / L, 420 g / L, 440 g / L, 460 g / L, 480 g / L, 500 g / L, 520 g / L, 540 g / L, 560 g / L, 580 g / L, 600 g / L or a range consisting of any two values.
[0030] In order to further improve the wear resistance and air permeability of the polyetheretherketone composite material, the polyetheretherketone composite material preferably includes 55-65wt% polyetheretherketone, 28-32wt% polytetrafluoroethylene and 7-13wt% porous glass microbeads.
[0031] In order to further improve the air permeability of the polyetheretherketone composite material, the mass ratio of the first porous glass microbeads to the second porous glass microbeads is preferably (25-35): (75-65).
[0032] In some specific embodiments, a matrix glass (the matrix glass contains SiO2, Na2O and B2O3, wherein the SiO2 content is 80wt%), boric acid and soda ash are mixed in a mass ratio of 77:19:4, and then melted at a temperature of 1470°C for 5.5 hours to obtain a glass mixture. The glass mixture is sequentially quenched and dried to obtain a glass body. The glass body is crushed and then placed in a spheroidizing furnace. At 1300°C, a flame spraying method is used to atomize the molten glass liquid through a nozzle into tiny droplets. The droplets rapidly expand and form a sphere in a high-temperature flame. Glass microbeads with an average particle size of 1 to 10 μm are obtained by screening. The glass microbeads are placed in a corundum crucible, heated to 590°C, kept warm for 20 hours, and cooled to room temperature. Placed in a 1.5 mol / L hydrochloric acid solution, heated to 70°C, and acid leached for 30 hours. Then, by washing and drying, the first porous glass microbeads with an average particle size of 1 to 5 μm and an average pore size of 20 to 50 nm are screened, and the glass microbeads have a connected pore structure. By screening glass microbeads with a larger average particle size and adjusting the acid solution concentration and the acid leaching time, the second porous glass microbeads with an average particle size of 20 to 30 μm and an average pore size of 60 to 100 nm can be screened.
[0033] In another typical embodiment of the present application, a method for preparing the polyetheretherketone composite material provided in the above-mentioned first typical embodiment is provided, comprising the following steps: mixing polyetheretherketone, polytetrafluoroethylene, a first porous glass microbead and a second porous glass microbead; and then performing melt granulation to obtain the polyetheretherketone composite material.
[0034] The preparation method of the polyetheretherketone composite material provided by the present application has simple operation steps and is suitable for industrial production. And the present application utilizes the self-lubricating property of polytetrafluoroethylene and the porous structure of porous glass microbeads, and the synergistic effect between polyetheretherketone, polytetrafluoroethylene and porous glass microbeads of a specific mass ratio makes the polyetheretherketone composite material not only have a lower friction coefficient and excellent wear resistance, but also have excellent air permeability. Especially when two porous glass microbeads of different particle sizes are compounded and used in a specific mass ratio, the two cooperate with each other to form a pore network, further improving the air permeability of the polyetheretherketone composite material. The polyetheretherketone composite material provided by the present application can be applied to seals, bearings and sliding structural parts in complex working environments.
[0035] In order to further promote the melting of the components, the temperature of the melt granulation is preferably 340-400°C.
[0036] Typically but not limiting, the temperature of melt granulation is 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C or a range consisting of any two of these values.
[0037] In a third typical embodiment of the present application, there is provided an application of the polyetheretherketone composite material provided in the first typical embodiment or the polyetheretherketone composite material obtained by the preparation method provided in the second typical embodiment in seals and / or bearings.
[0038] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.
[0039] Example 1
[0040] The present embodiment provides a polyetheretherketone composite material and a preparation method thereof, wherein the polyetheretherketone composite material comprises 60wt% polyetheretherketone (product model PEEK-G-A4), 30wt% polytetrafluoroethylene (product model PTFE SM 031) and 10wt% porous glass microbeads; wherein the porous glass microbeads comprise first porous glass microbeads and second porous glass microbeads, and the mass ratio of the two is 30:70. The average particle size of the first porous glass microbeads is 1 to 5 μm, and the average pore size of the first porous glass microbeads is 20 to 50 nm; the average particle size of the second porous glass microbeads is 20 to 30 μm, and the average pore size of the second porous glass microbeads is 60 to 100 nm.
[0041] The polyetheretherketone composite material is prepared according to the following steps: polyetheretherketone, polytetrafluoroethylene, first porous glass microbeads and second porous glass microbeads are mixed, and then melt-granulated at 360° C. to obtain the polyetheretherketone composite material.
[0042] Example 2
[0043] The difference from Example 1 is that Example 2 adjusts the content of each component in the polyetheretherketone composite material, so that the polyetheretherketone composite material includes 50wt% polyetheretherketone, 35wt% polytetrafluoroethylene and 15wt% porous glass microbeads, and the composition of the porous glass microbeads is the same as that of Example 1.
[0044] Example 3
[0045] The difference from Example 1 is that Example 3 adjusts the content of each component in the polyetheretherketone composite material, so that the polyetheretherketone composite material includes 70wt% polyetheretherketone, 25wt% polytetrafluoroethylene and 5wt% porous glass microbeads, and the composition of the porous glass microbeads is the same as that of Example 1.
[0046] Example 4
[0047] The difference from Example 1 is that Example 4 adjusts the content of each component in the polyetheretherketone composite material, so that the polyetheretherketone composite material includes 55wt% polyetheretherketone, 32wt% polytetrafluoroethylene and 13wt% porous glass microbeads, and the composition of the porous glass microbeads is the same as that of Example 1.
[0048] Example 5
[0049] The difference from Example 1 is that Example 5 adjusts the content of each component in the polyetheretherketone composite material, so that the polyetheretherketone composite material includes 65wt% polyetheretherketone, 28wt% polytetrafluoroethylene and 7wt% porous glass microbeads, and the composition of the porous glass microbeads is the same as that of Example 1.
[0050] Example 6
[0051] The difference from Example 1 is that, in Example 6, the mass ratio of the first porous glass microbeads to the second porous glass microbeads in the porous glass microbeads is adjusted so that the mass ratio of the two is 20:80.
[0052] Example 7
[0053] The difference from Example 1 is that, in Example 7, the mass ratio of the first porous glass microbeads to the second porous glass microbeads in the porous glass microbeads is adjusted so that the mass ratio of the two is 40:60.
[0054] Example 8
[0055] The difference from Example 1 is that, in Example 8, the mass ratio of the first porous glass microbeads to the second porous glass microbeads in the porous glass microbeads is adjusted so that the mass ratio of the two is 25:75.
[0056] Example 9
[0057] The difference from Example 1 is that, in Example 9, the mass ratio of the first porous glass microbeads to the second porous glass microbeads in the porous glass microbeads is adjusted so that the mass ratio of the two is 35:65.
[0058] Comparative Example 1
[0059] The difference from Example 1 is that in Comparative Example 1, the content of each component in the polyetheretherketone composite material is adjusted so that the polyetheretherketone composite material includes 30wt% polyetheretherketone, 10wt% polytetrafluoroethylene and 60wt% porous glass microbeads, and the composition of the porous glass microbeads is the same as that in Example 1.
[0060] Comparative Example 2
[0061] The difference from Example 1 is that in Comparative Example 2, the content of each component in the polyetheretherketone composite material is adjusted so that the polyetheretherketone composite material includes 90wt% polyetheretherketone, 8wt% polytetrafluoroethylene and 2wt% porous glass microbeads, and the composition of the porous glass microbeads is the same as that in Example 1.
[0062] Comparative Example 3
[0063] The difference from Example 1 is that in Comparative Example 3, porous glass microbeads are not added, so that the polyetheretherketone composite material includes 70 wt % of polyetheretherketone and 30 wt % of polytetrafluoroethylene.
[0064] Comparative Example 4
[0065] The difference from Example 1 is that in Comparative Example 4, polytetrafluoroethylene is not added, so that the polyetheretherketone composite material includes 90 wt % of polyetheretherketone and 10 wt % of porous glass microbeads, and the composition of the porous glass microbeads is the same as that of Example 1.
[0066] Comparative Example 5
[0067] The difference from Example 1 is that in Comparative Example 5, the mass ratio of the first porous glass microbeads to the second porous glass microbeads in the porous glass microbeads is adjusted so that the mass ratio of the two is 5:95.
[0068] Comparative Example 6
[0069] The difference from Example 1 is that in Comparative Example 6, the mass ratio of the first porous glass microbeads to the second porous glass microbeads in the porous glass microbeads is adjusted so that the mass ratio of the two is 70:30.
[0070] Test Case
[0071] The polyetheretherketone composite materials obtained in the examples and comparative examples were injection molded into standard specimens, and friction tests and air permeability tests were performed. The results are shown in Table 1.
[0072] 1. According to GB / T 10006-2021 "Determination of friction coefficient of plastic films and sheets", carry out dynamic friction coefficient test.
[0073] 2. Refer to GB / T5453-1997 standard to test the gas permeability of polyetheretherketone composite material samples.
[0074] Table 1
[0075]
[0076]
[0077] When the polyetheretherketone composite material includes 50-70wt% polyetheretherketone, 25-35wt% polytetrafluoroethylene and 5-15wt% porous glass microbeads; the porous glass microbeads include first porous glass microbeads and second porous glass microbeads, and the mass ratio of the two is (20-40): (80-60), the polyetheretherketone composite material has excellent friction resistance and air permeability. When the components or proportions of the polyetheretherketone composite material are changed, the polyetheretherketone composite material cannot have both excellent friction resistance and air permeability.
[0078] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0079] The present application utilizes the self-lubricating property of polytetrafluoroethylene and the porous structure of porous glass microbeads, and through the synergistic effect between polyetheretherketone, polytetrafluoroethylene and porous glass microbeads of a specific mass ratio, the polyetheretherketone composite material not only has a lower friction coefficient and excellent wear resistance, but also has excellent air permeability. Especially when two porous glass microbeads with different particle sizes are compounded and used in a specific mass ratio, the two cooperate with each other to form a pore network, further improving the air permeability of the polyetheretherketone composite material. The polyetheretherketone composite material provided in the present application can be applied to seals, bearings and sliding structural parts in complex working environments.
[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A polyetheretherketone composite material, characterized in that: The polyetheretherketone composite material comprises 50-70wt% polyetheretherketone, 25-35wt% polytetrafluoroethylene and 5-15wt% porous glass beads; the porous glass beads comprise first porous glass beads and second porous glass beads, and the mass ratio of the two is (20-40):(80-60); wherein the average particle size of the first porous glass beads is 1-5μm, and the average particle size of the second porous glass beads is 20-30μm.
2. The polyetheretherketone composite material according to claim 1, characterized in that: The average pore diameter of the first porous glass microbeads is 20-50 nm.
3. The polyetheretherketone composite material according to claim 1, characterized in that: The average pore diameter of the second porous glass microbeads is 60-100 nm.
4. The polyetheretherketone composite material according to claim 1, characterized in that: The polyetheretherketone includes at least one of PEEK-G-A2, PEEK-G-A3, and PEEK-G-A4.
5. The polyetheretherketone composite material according to claim 1, characterized in that: The model of the polytetrafluoroethylene is PTFESM 031.
6. The polyetheretherketone composite material according to any one of claims 1 to 5, characterized in that: The polyetheretherketone composite material comprises 55-65wt% of the polyetheretherketone, 28-32wt% of the polytetrafluoroethylene and 7-13wt% of the porous glass microbeads.
7. The polyetheretherketone composite material according to any one of claims 1 to 5, characterized in that: The mass ratio of the first porous glass microbeads to the second porous glass microbeads is (25-35):(75-65).
8. The method for preparing the polyetheretherketone composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The polyetheretherketone, the polytetrafluoroethylene, the first porous glass microbeads and the second porous glass microbeads are mixed, and then melt-granulated to obtain the polyetheretherketone composite material.
9. The method for preparing the polyetheretherketone composite material according to claim 8, characterized in that: The temperature of the melt granulation is 340-400°C.
10. Use of the polyetheretherketone composite material according to any one of claims 1 to 7 or the polyetheretherketone composite material obtained by the preparation method according to claim 8 or 9 in seals and / or bearings.